2020
DOI: 10.1007/978-3-030-39081-5_12
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive RBF Interpolation for Estimating Missing Values in Geographical Data

Abstract: The quality of datasets is a critical issue in big data mining. More interesting things could be mined from datasets with higher quality. The existence of missing values in geographical data would worsen the quality of big datasets. To improve the data quality, the missing values are generally needed to be estimated using various machine learning algorithms or mathematical methods such as approximations and interpolations. In this paper, we propose an adaptive Radial Basis Function (RBF) interpolation algorith… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Of course, it is also suggested that to choose more interpolatory points uniformly for data collection. In the future, the refined partition of unity will be considered and the large scale real scattered data (e.g., geographical data [18]) will be tested.…”
Section: Resultsmentioning
confidence: 99%
“…Of course, it is also suggested that to choose more interpolatory points uniformly for data collection. In the future, the refined partition of unity will be considered and the large scale real scattered data (e.g., geographical data [18]) will be tested.…”
Section: Resultsmentioning
confidence: 99%
“…Various methods of data interpolation, such as mean imputation [12], local least-squares fitting [13], and k-nearest neighbors (KNN) [14], were widely used to fill the missing values [15] before analysis. State-of-the-art interpolating Atmosphere 2022, 13, 1473 2 of 16 methods include an adaptive radial basis function (RBF) interpolation algorithm by [16], a multidimensional interpolating based on long short-term memory (LSTM) [17], and a combination of KNN and random forest algorithm (RF-KNN) [18]. The methods mentioned above could consider either the spatial or temporal relationship of data and provide reasonable interpolating solutions, but air quality data are influenced by time and location at the same time, considering that either spatial or temporal characteristics likely results in a large error.…”
Section: Introductionmentioning
confidence: 99%